(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The problem of applying modern psychological and pedagogical technologies n educational process of technical institution of higher education to form students’ interpersonal relationships has been studied Common technologies which encourage forming interpersonal relationships were defined; recent dissertation researches studying this problem were analyzed.